Application of green seaweed biomass for MoVI sorption from contaminated waters. Kinetic, thermodynamic and continuous sorption studies - Bertoni, Fernando Ariel (2015)
Spongomorpha pacifica biomass was evaluated as a new sorbent for MoVI removal from aqueous solution. The maximum sorption capacity was found to be 1.28 106 ± 1 104 mg kg1 at 20 C and pH 2.0. Sorption kinetics and equilibrium studies followed pseudo-first order and Langmuir adsorption isotherm models, respectively. FTIR analysis revealed that carboxyl and hydroxyl groups were mainly responsible for the sorption of MoVI. SEM images show that morphological changes occur at the biomass surface after MoVI sorption. Activation parameters and mean free energies obtained with Dubinin-Radushkevich isotherm model demonstrate that the mechanism of sorption process was chemical sorption. Thermodynamic parameters demonstrate that the sorption process was spontaneous, endothermic and the driven force was entropic. The isosteric heat of sorption decreases with surface loading, indicating that S. pacifica has an energetically non-homogeneous surface. Experimental breakthrough curves were simulated by Thomas and modified dose?response models. The bed depth service time (BDST) model was employed to scale-up the continuous sorption experiments. The critical bed depth, Z0 was determined to be 1.7 cm. S. pacifica biomass showed to be a good sorbent for MoVI and it can be used in continuous treatment of effluent polluted with molybdate ions.